KOMUNIKASI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBELAJARAN JARAK JAUH MASA PANDEMI COVID-19 DI SEKOLAH DASAR ISLAM TERPADU - Hadi Widodo; Yenni Fitri; Syafaruddin Syafaruddin; Dedi Sahputra Napitupulu (Universitas Muria Kudus, 2021)
The purpose of this study is to describe the communication of Islamic Religious Education (PAI) teachers during distance learning and the inhibiting factors.The research method used is a qualitative phenomenological method. The research location is at SD IT Al-Kaffah Binjai which is located at Jl. Jamin Ginting No. 35, district. South Binjai, North Sumatra Province. The research was conducted in September-December 2020. The main data sources of the research are informants, while the secondary data sources are documents (archives, learning tools, and others). Collecting data using interview, observation, and document techniques. Interviews were addressed to teachers and students as informants. The data validity technique used is source triangulation. The data analysis technique used is Interpretative Phenomenological Analysis. The stages of Interpretative Phenomenological Analysis carried out are as follows: 1) Reading and re-reading; 2) Initial notes; 3) Developing Emergent themes; 4) Searching for connections across emergent themes; 5) Moving the next case; and 6) Looking for patterns across cases.The results of the study indicate that the activity of communicating learning through distance has been running quite effectively but in its implementation it is still not optimal as a whole and evaluation and solutions are needed to be able to improve the process of distance learning activities running more efficiently.